A Bibliometric Analysis of Health Gamification Research Using Vosviewer - Stefanus Andika Setyawan; Siswono Akuan Rokanta (Syntax Corporation, 2022)
Changes in people's lifestyles are suspected to be one of the causes of a shift in disease patterns (known as epidemiological transition) in the last 30 years. In the 1990s, infectious diseases such as Upper Respiratory Tract Infection (ARI), Tuberculosis (TBC), and Diarrhea were the leading causes of death. To prevent the worsening of this shift in disease patterns, media that can provide information is necessary to guide people towards healthier lifestyles. Gamification is one of the interactive learning concepts that can be implemented to promote Health education. Gamification can be implemented on mobile platforms, making it accessible for anyone to get health education in a fun way, no matter where they are. To obtain information about Health Gamification studies, we used the Google Scholar database. We used topic areas with titles, keywords, and abstract criteria in Health Gamification studies as a reference for extracting search results. We used VOSviewer to extract search results. After that, the results of bibliometric mapping were analyzed further. We found a total of 1000 articles in the Google Scholar database accessed on February 24, 2023. We analyzed how many articles have been published about Health Gamification and its relationships to topic areas using VOSViewer. This review can provide a reference point for further research related to promoting Health Education.